Knowledge and opinions of primary and secondary school students regarding their "musculoskeletal health" and the correct body posture (CBP) - Ξυδέα-Κικεμένη, Αναστασία; Τσέρτος, Γεώργιος (Education Sciences, 2023)
"Musculoskeletal health" is especially important today, mainly because of the increasing sedentary behavior. Musculoskeletal disorders and general health problems in adults can appear as early as childhood and for this reason, prevention and education in Correct Body Posture (CBP) is worldwide promoted. The purpose of the study was to investigate the knowledge and opinions of primary and secondary school students regarding their musculoskeletal strain and CBP. The research was carried out with a self-completed questionnaire, in 2021 on 1327 primary, secondary and high school students of Trikala and Livadia. Statistical processing was done with SPSS and the application of appropriate tests. The sample consisted of 50.5% boys and 49.5% girls, with an average age of 14.6±2.2 years. Regarding their knowledge/opinions, they know that bad posture is responsible for various diseases, that the weight of the school bag causes musculoskeletal problems and that the posture on the mobile phone/PC can cause pain in the back & neck. Also they consider CBP necessary in their lives, but for which they are not trained. Interesting statistical results emerged regarding gender and age. In conclusion, the development of complex health promotion actions and programs is considered necessary.